2014
DOI: 10.3390/molecules190914114
|View full text |Cite
|
Sign up to set email alerts
|

RP-HPLC Characterization of Lupenone and β-Sitosterol in Rhizoma Musae and Evaluation of the Anti-Diabetic Activity of Lupenone in Diabetic Sprague-Dawley Rats

Abstract: With the aim of characterizing the active ingredients lupenone and β-sitosterol in Rhizoma Musae samples a reversed-phase HPLC method for the separation of these two compounds in Rhizoma Musae samples was developed (regression coefficient > 0.9996). The method was further applied to quantify lupenone and β-sitosterol content in Rhizoma Musae samples cultured in different growth environments. Different variables such as geographical location, growth stage, and harvest time, demonstrated differential effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…According to reports, lupenone can inhibit α -glucosidase ( α -Glu) and protein tyrosine phosphatase 1B (PTP1B) activity in vitro [31,32], the two enzymes are associated with anti-diabetic, and recently study has found that lupenone has the anti-diabetic activity in diabetic sprague-dawley rats [33]. In this study, the results clearly showed that lupenone had a significantly antihyperglycemic activity in alloxan-induced diabetic mice with no animal deaths during the experiment.…”
Section: Antihyperglycemic Effect Of Lupenone In Diabetic Micementioning
confidence: 99%
“…According to reports, lupenone can inhibit α -glucosidase ( α -Glu) and protein tyrosine phosphatase 1B (PTP1B) activity in vitro [31,32], the two enzymes are associated with anti-diabetic, and recently study has found that lupenone has the anti-diabetic activity in diabetic sprague-dawley rats [33]. In this study, the results clearly showed that lupenone had a significantly antihyperglycemic activity in alloxan-induced diabetic mice with no animal deaths during the experiment.…”
Section: Antihyperglycemic Effect Of Lupenone In Diabetic Micementioning
confidence: 99%
“…Comparing with the established HPLC method (19), the present method had a saved (85%) mobile phase, shorter (50%) analysis time and greatly improved resolution and sensitivity. This method was applicable to determination of a large number of Rhizoma Musae samples, and it can reduce pollution and protect the environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lupenone and β-sitosterol were selected as index components in Rhizoma Musae, because some literature has shown that the lupenone and β-sitosterol have anti-diabetic activity (18,19), so the two components were selected as index components in Rhizoma Musae to control the herb quality. For the simultaneous analysis of lupenone and β-sitosterol in Rhizoma Musae, a fast, reliable and sensitivity UPLC with DAD and ELSD method was developed, the method was validated in specificity, linearity, precision Y is the peak area in DAD chromatograms monitored at 206 nm, X is the compound concentration (µg/mL) injected, and y and x are the logarithmic values of area and concentration injected in ELSD chromatograms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations